Estilo pra vida : criação de si em Nietzsche - Alice Mendes Melo (2018)
In the present dissertation, we intend to vindicate self-creation as a substitute for the traditional moral standard in Nietzsche’s middle period. Therefore, we define self-creation as bringing style to life, setting the discussion between a naturalist approach, in which physiology has unnegotiable value, and narrativism, in which the role of consciousness and interpretation of natural world is recalled. Lastly, we conclude that style to life emerge in the tension between will to truth and will to appearance.